ANALISIS MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA MATERI NILAI UANG PECAHAN KELAS II SD NEGERI PASAR BARU I TANGERANG - Iis Susilawati; Saktian Dwi Hartantri; Arry Patriasurya Azhar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe students' interest in learning mathematics on the subject of monetary values in fractions of SD Negeri Pasar Baru I Tangerang. Based on preliminary studies through interviews with teachers and students, students' interest in learning mathematics during the material value of fractional money material was quite good. This can be seen from the students who pay attention to the teacher's explanation, concentrate and actively participate in learning mathematics on the subject of fractional monetary values. This type of research is descriptive qualitative. The subjects in this study were all students of grade II, which amounted to 34 students. The method used in research on students' interest in learning mathematics is the subject matter of fractional monetary values by collecting observational data, interviews and documentation studies. Interviewing students' learning interest in learning mathematics on the subject of fractional monetary values consists of 15 questions taken from four indicators 1) feeling happy; 2) student interest; 3) student attention; 4) student engagement. The results of the study proved that students' interest in learning mathematics in fractional money material was quite good.